Transcriptome sequencing reveals significant RNA variation in human sperm samples - Weiming Chen; Lei Yu; Zhenyu Jia; Jianguo Zhu (BMC Research Notes)
Abstract DNA transcription and protein translation are non-coupled for life activities after sperm formation, and if the RNA profile of isolated spermatozoa is resolved, it will help men with epigenetic effects on their offspring and male infertility due to RNA disorders. However, the significance of RNA identity, quantity, and quality in sperm biology and their implications for male fertility are not well understood. We collected 83 semen samples, including with normal sperm motility and with asthenospermia, a condition characterized by reduced sperm motility, for transcriptome sequence. Due to the inherently low RNA content in sperm, only 37 samples were successfully sequenced. Among these, 15 samples met high-quality standards with an RNA Integrity Number (RIN) greater than 6 and a 28 S/18S ratio greater than 0.7, while 22 samples had a RIN between 5 and 6 with a 28 S/18S ratio greater than 0.7. To foster broader research, we have made the RNA sequencing data of these two sets of samples publicly available in the GSA-Human database, under accession numbers HRA006250 and HRA006906, respectively. The data could help develop new algorithms to parse the RNA landscape retained after sperm formation, while potentially discovering new molecular markers of weak asthenospermia.